A rare presentation of immune thrombocytopenic purpura - Yadav, Ponvijaya; Gokhale, Vijayashree S.; Parati, Rupesh; Mehta, Keyuri (International Journal of Research in Medical Sciences, 2021)
Immune thrombocytopenic purpura (ITP) is defined as a hematologic disorder, characterized by isolated thrombocytopenia without any apparent cause. Some patients may be diagnosed during routine blood investigations or may present with bleeding diathesis. Treatment required for moderate to severe thrombocytopenia or those with bleeding manifestations. We present a case of 43 year old male, sputum positive pulmonary tuberculosis on isoniazid (H), rifampin (R), pyrazinamide (Z), and ethambutol (E) (HRZE) with persistent thrombocytopenia. He developed hepatitis hence isoniazid (INH) and rifampicin were stopped. He had fever, rash, purpura, hematuria and blood tinged sputum with platelet count of 10,000. 4 random donor platelets (RDPs) given. He suffered from mild COVID-19 infection and recovered in 2 weeks but platelets remained low. Bone marrow examination was suggestive of ITP. Inspite of steroid therapy no improvement was seen. Later was treated with injection romiplostim, and started on systemic lupus erythematosus (SLE) regimen for tuberculosis and discharged with regular follow up. Last platelet count being 1,20000/dl, liver function tests normal and now restarted on HRZE.